2004
DOI: 10.1081/amp-200028077
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Pressure Compaction of Tungsten Powders

Abstract: Compacts of tungsten powders were consolidated by Plasma Pressure Compaction (P 2 C), an electric discharge technique. The powders were a variety of commercially available grades ranging in average particle size from submicron to 12 microns. Following consolidation, the density of the compacts was measured, and the microstructure examined. Results revealed the effect of powder size, pulsed current treatment, final hold temperature, and applied pressure on final part density and microstructure development. Most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…The starting size of the tungsten powder particles and the processing parameters used to obtain the bulk samples are summarized in Table 1. Additional details of the P 2 C technique can be found elsewhere [31][32][33][34][35][36][37]. A schematic of the test set up is shown in Fig.…”
Section: Sample Preparation By Consolidationmentioning
confidence: 99%
See 1 more Smart Citation
“…The starting size of the tungsten powder particles and the processing parameters used to obtain the bulk samples are summarized in Table 1. Additional details of the P 2 C technique can be found elsewhere [31][32][33][34][35][36][37]. A schematic of the test set up is shown in Fig.…”
Section: Sample Preparation By Consolidationmentioning
confidence: 99%
“…Thus, it is essential to minimize grain growth through a careful control of the consolidation parameters, namely: (i) temperature, (ii) pressure, and (iii) time of consolidation. To this end, the technique of plasma pressure compaction (referred to henceforth in this technical manuscript as P 2 C) has shown the capability of being both an efficient and effective field-activated sintering technique that has been used to successfully consolidate ceramic, metallic and even intermetallic powders to near theoretical density [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…This study indicated clean grain boundaries formed due to the interface cleaning effect by the SPS method [5,9]. Cho et al tested various SPS sintering conditions and revealed the effects of the powder size, pulsed current, holding temperature and pressure on the final density and microstructure of W specimens [10].…”
Section: Introductionmentioning
confidence: 84%
“…x ~ (D C t) 0.5 (10) where x is the tungsten carbide thickness, D C is the diffusion coefficient of carbon into W (cm 2 /s) and t is time. D C is estimated to be 3.86 × 10 -7 cm 2 /s, which is in a good agreement with a literature value [49].…”
Section: Microstructure Characterizationmentioning
confidence: 99%
“…Still, HIP is limited to pressures of 300 MPa at temperatures of 17008C, which may not be sufficient for the most difficult to densify refractory metals. Other pressure-assisted consolidation techniques, such as rapid omni-directional compaction (ROC) and spark plasma sintering (SPS) have been used to densify W (Cho et al, 2006;Paramore et al, 2007), but these methods do not seem practical for net-shape MIM components.…”
Section: Practical Process Concernsmentioning
confidence: 97%